The Role and Strategy of Islamic Organization (Muhammadiyah) in Realizing Sustainable Development Goals in Indonesia - Tofan Tri Nugroho; Eko Hardiansyah; Diah Krisnaningsih (Jurnal Manajemen Indonesia, 2025)
This article explores the role and strategies of the Muhammadiyah organization in contributing to the realization of the Sustainable Development Goals (SDGs) in Indonesia. Muhammadiyah has evolved from its initial focus on modernizing Islamic education to impacting various sectors such as health, economy, and social responsibility. This research employs a descriptive qualitative approach using ethnographic analysis techniques, including interviews and observations, to examine Muhammadiyah's contributions. The findings highlight the organization's important role in education, health, and economic development, as well as its plans to expand into new sectors such as mining and pharmaceutical production. This study underscores Muhammadiyah's potential to further contribute to sustainable development in Indonesia. Keywords : Ethnographic; Muhammadiyah; SDGs; Strategies